Growth responses and secondary metabolites properties of three accessions of Justicia gendarussa burm f. affected by plant age, water stress and chicken manure - Rahmat, Mohd Hafizad (2020)
Justicia gendarussa Burm F., (family: Acanthaceae) have been used to treat diseases in the traditional medicine. Many pharmacological studies have demonstrated that this plant is beneficial for human health and has the potential for commercialization due to its therapeutic properties. Morphological and secondary metabolites changes in plants can occur naturally during the growth periods as to be influenced by of environmental factors. Therefore, this study aimed to evaluate the effects of accessions, plant age, water stress, and chicken manure on the growth of J. gendarussa based on biomass, morphological characters, and secondary metabolites compounds (phenolic (TPC) and flavonoid (TFC)) Two glasshouse experiments were carried out at glasshouse complex at Field 2, Faculty of Agriculture, Universiti Putra Malaysia. The first experiment aimed to examine the effects of plant age on growth, gas exchange attributes, and secondary metabolites of three J. gendarussa accessions (‘Black stem’; JGB, ‘Green stem’; JGG, and, ‘Variegata’; JGV). The treatments were laid in a randomized complete block design (RCBD) and blocked five times. The second experiment was design to evaluate the effect of water stress (100%, 75%, 50%, and 25% of evapotranspiration replacement, ET-R) and chicken manure application (0 kg N ha-1 and 90 kg N ha-1) on growth, gas exchange attributes as well as secondary metabolites of J. gendarussa. The treatments were laid out in RCBD with three blocks. The recorded parameters were measured within three regular intervals of every four weeks at 4, 8, and 12 WAT and were statistically analysis. Among three accessions evaluated at three different plant ages, JGG exhibited the highest dry weight at each observation weeks (3.9 g to 11.5 g). This JG accession also produced highest growth (for example 42% to 162% higher in leaves number than other accessions) at 12 WAT. For the secondary metabolites evaluation had shown that JGB exhibited a highest TPC and TFC at 8 WAT of plant ages (0.75 mg GAE g-1 DW), and TFC (0.39 mg QE g-1 DW). As plant became older (12 WAT), JGG exhibited a highest dry weight and total secondary metabolite production (TPC: 4.2 mg GAE; TFC: 2.60 mg QE). Therefore, JGG was then chosen to be used in the second experiment. The combined treatments of water stress and chicken manure did not affected growth as well as secondary metabolite production in JGG. However, water stress had significantly (p≤0.01) affected most of the growth, and physiological attributes of JGG which reduced to 3.5% to 7% as the water stress severity increased compared to control (4.4g). In contrast, secondary metabolites accumulations were increased under the water stress, especially at level of w50, which demonstrated the highest total production in JGG at 12 WAT. The highest secondary metabolites production was recorded in JGG exposed to water stress at 50% ET-R (TPC: 0.9 mg GAE g-1 DW dan TFC: 0.37 mg QE g-1 DW. The chicken manure application at 90 kg N ha-1 (n90) had significant improved 2.7% of total dry weigh JGG. However, the chicken manure application had no significant (p<0.05) effect on the secondary metabolites’ accumulation and total production. This study suggests that accessions, plant age, water stress, and chicken manure had significantly affected the growth and secondary metabolites of J. gendarussa. JGG harvest at age of 12 WAT and subjected to 50% ET-R of water stress level have shown to yield different amount of secondary metabolites production (TPC and TFC). Additional chicken manure application improved growth attributes of JGG. Thus, cultivation of JG based on the suggestion made from this study may increase its potential in bio business, which can further aid the socio-economic farming community in Malaysia.